Pengembangan Sistem Informasi Untuk Menentukan Prioritas Pemberian Kredit dengan Metode Promethee - Sujarwo, Sujarwo (JSINBIS (Jurnal Sistem Informasi Bisnis), 2015)
This study develops an information system for decision-making on priority lending and introduce new information into the decision-making process resulting in the selection process more realistic.The method used in this research method PROMETHEE "Preference Ranking Organization Method for Enrichment Evaluation" is used in a decision support system for its simplicity, clarity, and stability with the assessment of several alternative criteria for determining the order of decision making (priority) in the multicriteria analysis. After that, compared with the manual calculation of the bank. This method can be applied to all types of decision-making problems with heterogeneous information and multigranular. The result of this study is that the information system built to produce a ranking as follows: A prospective customers rank 1, C rank 2, B rank 3, E rank 4, D rank 5, and F rank 6, then compared that with the manual there is a difference ranking ranking which puts prospective customers in rank F 4 which turns the loan installment payments problems occur. Keywords: Promethee; Rank; Decision Making System.